(untitled) (Physical Education, Health and Social Sciences, 2026)
Medication administration errors are some of the highest-priority and avoidable patient safety issues facing the nursing practice of hospitals around the world, and the interruption in medication preparation and administration is one of the most significant and alterable risk factors. This paper has looked at how a structured multicomponent intervention of interruption-reduction program works well in enhancing medication administration safety among registered nurses at Aga Khan University Hospital (AKUH), Karachi, Pakistan, in the medical units. The quasi-experimental pre-test and post-test design was used with a purposive total population sample where 120 registered nurses were recruited in four similar inpatient medical units. The intervention package included four combined elements, including special medication preparation rooms, uniform Do Not Disturb graphic zoning, a medication-specific structured communication regimen, and a two-session staff sensitization educational program. The Medication Administration Error Observation Tool (MAEOT), which was tested and validated, was used to collect data during structured pre and post intervention observation time frames administered by trained independent observers. Findings showed statistically significant total frequency of interruption of 50.2 percent and overall rate of medication administration error reduction of 59.3 percent after interventions were implemented with the outcome measures of all outcome comparisons legalized at p =.05. Multivariate regression analysis determined the greatest independent predictors of the reduction of post-intervention errors to be baseline interruption frequency, Do Not Disturb protocol compliance and training attendance. The combined intervention was always better than all the individual ones in all the measured outcomes. These results confirm that purposeful, evidence-based interruption-reduction initiatives can be performed, work, and contextually delivered in the context of Pakistani tertiary care, providing a model that can be repeated with medication safety enhancement in similar care settings in South Asia and other countries.